(3eONd JfXjej JcGedj JMdjdjs - (3QYO MSf(B, (3GdUQfs ((3OeTb(B:s (3OGQ GdQVGddfTQ(B,s, 2001)
(3efXeI GdJLGQI GdYGdejI,GdefXeI GdOhdjI ddehGUaGJ hGdebGjjS,UfOhb GdfbO GdOhdj hefgLjI MSGH eDTQ UfOhb GdfbO GdOhdj,GdHfc GdOhdj ddEfTGA hGdJYejQ,HYV GdefXeGJ GdCNQi GdeJNUUI aj eLGd GdJLGQI GdOhdjI,GdGSJKeGQ GdCLfHj GdeHGTQ,GdJcGed GdGbJUGOj GdOhdj,GdJcGed GdGbJUGOj GdYQHj,GdTQGcI GdChQhHjI(B-(3GdeJhSWjI,HYV feGPL GdYdGbGJ GdGbJUGOjI GdOhdjI dShQjG,NUGFU GdGbJUGOGJ GdYQHjI(B:(3ebGQfGJ aj GdJLGQI GdNGQLjI hCSYGQ GdUQa hehGRjf GdeOahYGJ,eSJbHd GdJLGQI GdOhdjIs
(3HHdjhZQGajG(B:(3U(B.535-542(3;agQS GdLOGhd(B:(3U(B.531-533s
Keywords: (3GdJLGQI GdNGQLjIs